Synthesis of manganese oxides for adsorptive removal of ammonia nitrogen from aqueous solutions. (1st November 2020) - Zhang, Lei; Wang, Junli; Qiao, Hongxia; Liu, Fuxing; Fu, Zishi
Abstract: In recent years, manganese oxides have been widely applied in pollution control, but not found to be used as NH3 –N adsorbent. In this study, synthetic manganese oxides (MnOs) prepared from the redox reaction between KMnO4 and MnSO4 were used to remove NH3 –N from aqueous solution. The influence of relative ratio of MnSO4 /KMnO4 on the yield, composition and NH3 –N removal was discussed for obtain the optimal adsorbent. Several characterization methods including XPS, Zeta potential, and FTIR, were introduced in this study. Removal of NH3 –N by MnOs under various environmental factors, such as initial pH, reaction time, coexisting cations and ambient temperature with different levels, was investigated subsequently. A few of kinetics and isotherm models were introduced to fit the experimental data, which were applied to figure out the NH3 –N removal mechanism for MnOs. The results indicated that manganese oxide derived from the redox reaction with the ratio of MnSO4 /KMnO4 set as 1:1 exhibited the highest removal despite the lower yield. The presence of superabundant Mn (Ⅱ) covering the surface of nascent MnO2 would reduce NH3 –N removal. The initial pH range of 6–8 is beneficial to the adsorption of NH3 –N and the highest adsorption capacity would occur at pH = 6. The influence of coexisting cations on NH3 –N removal follows an order of Ca 2+ > K + > Mg 2+ > Na +, and raising temperature can promote the elimination of NH3 –N. Pseudo-second-order kinetics and Langmuir fitting models were used for describing NH3 –N adsorption process. The electrostatic interaction and ion exchange between hydroxyl and NH4 + were the dominant removal mechanism. Manganese oxides were expected to be promising for the control of NH3 –N pollution in water bodies due to simple preparation procedure, rapid adsorption process and higher adsorption capacity. Graphical abstract: Image 1 Highlights: Synthetic manganese oxide (MnOs) can be synthesized through redox reaction between KMnO4 and MnSO4 . MnOs1 prepared with a lower ratio of KMnO4 /MnSO4 designed as 1:1 shew best performance for adsorption of NH3 –N. Electrostatic interaction and ion exchange are the dominant contribution for NH3 –N adsorption. The adsorption of NH3 –N onto MnOs1 is an endothermic and monolayer adsorption process.